P118 Should we treat or rescreen patients first with equivocal chlamydia and gonorrhoea naat results?. (18th May 2015) - Ovens, Katie; Smit, Erasmus; Barrett, Sarah
Abstract : Background/introduction: Equivocal NAAT results for Chlamydia and gonorrhoea (GC) cause treatment dilemmas for health professionals as there are no definitive management guidelines. Debate continues whether to rescreen and treat patients with equivocal results or rescreen the patient and await results before treatment. Aim(s)/objectives: To investigate rescreening tests for equivocal results and establish when patients should be offered treatment. Methods: A retrospective study of equivocal results from 2 GUM clinics between November 2013 and May 2014, and a third clinic between March 2010 and May 2014. HIV positive patients' results were included. Paper notes or electronic systems were examined. Data was collected using a standardised proforma and analysed using excel software. Results: 76 equivocal results (2.2% of positive results) were investigated. 62 patients (83.8%) attended recall appointments, 36 patients (58.0%) were offered treatment and rescreened, 14 (22.6%) were rescreened and awaited results prior to treatment and 2 patients (3.2%) were treated with no retest sent. 8 patients (16.1%) were treated due to a positive GC result at a second site alongside the equivocal result. Of the 54 equivocal results re-tested, 3 (5.6%) were positive and all of these resulted from equivocal GC tests (19 rescreened). All 35 rescreened equivocal Chlamydia tests were negative. Discussion/conclusion: There is currently variation in how clinicians are managing equivocal results. The findings suggest that initiating treatment for Chlamydia before rescreening may result in over treatment. GC equivocal results are more likely to be positive on re-testing, thus clinicians should have a lower threshold for treating these at the time of rescreening.